Biocompatibility of Metal–Phenolic Network-Coated Nanoparticles - Anett Välimets; Kairi Koort; Monika Mortimer (Proceedings)
Metal–phenolic networks (MPNs) are novel adsorbent materials that have promising applications in the environmental remediation of organic pollutants and heavy metals [...]